Generalized Transformed Hough: Segmentation of Contours in Angiographic Images - Oscar Eduardo Gualdron (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The morphologic and functional study of cardiovascular system is of vital importance because problems related to this system are one of the main causes of   mortality in the world. It is important to mention that the left ventricle (VI) is the most susceptible to suffer severe damage, in diseases, such as arterial hypertension, mellitus diabetes or arteriosclerosis. This article presents a new methodology directed to segmentation of left ventricular contours, in angiographic images by using Generalized Hough Transform (TGH). It is important to obtain the ventricular edge, because analyzing processes of systole and diastole end, it is possible to calculate parameters of the cardiac functionality as the end-diastolic volume, end systolic volume, ejection fraction, cardiac output, Hyperkinéticos, Hypokinéticos segments, and normal; in this work we focus only on the removal of the same.